QOL-15. VISUAL IMPAIRMENT AND AUDITORY COMPENSATION IN CHILDREN TREATED FOR OPTIC PATHWAY GLIOMA. Issue 2 (22nd June 2018) - Papini, Chiara; Pitchford, Nicola; Dineen, Rob; Walker, David
Abstract: Survivors of paediatric Optic Pathway Glioma (OPG) experience varying degrees of visual impairment. Yet sparse research has examined the impact of brain damage and the resulting vision loss on cognitive development and scholastic progression, and to date, no studies have investigated potential compensatory mechanisms and strategies in auditory functioning, as is reported in visually impaired individuals. This study describes the motor, cognitive, and scholastic abilities in a cohort of 12 children, aged 6-13 years, diagnosed with OPG and treated with observation and/or chemotherapy. Analogous tasks that rely on either visual or auditory input were used to assess core skills, including fine motor coordination, attention, memory, spoken English comprehension, and mathematics. Results showed no significant difference between visual and auditory performance across abilities. Only visual and auditory performance of the two scholastic abilities were associated, suggesting that a common mechanism might underpin complex capabilities crucial for school performance irrespective of the sensory modality of the task, while different visual and auditory neural processes could sustain specific motor and cognitive skills. Visual acuity in the best eye did not correlate with performance in visually-based behavioural tasks, suggesting no direct association between low-level sensorial experience and high-level cognition in the visual domain. Overall, these results demonstrate no evident compensation for the vision loss through the auditory channel and highlight the importance of including multiple sensory modalities in the neuropsychological follow-up assessment for these children. These results need to be corroborated with a larger sample of paediatric patients for generalisation at a population level.